1989
DOI: 10.1007/bf00274535
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish childhood diabetes study III: IgM against coxsackie B viruses in newly diagnosed Type 1 (insulin-dependent) diabetic children ? no evidence of increased antibody frequency

Abstract: Summary. Sera from essentially all Swedish children aged 0-14 years with Type 1 (insulin-dependent) diabetes mellitus with onset during an autumn period (October-December 1985) and a late spring period (May-June 1986) were selected. In all, 98 patients were analysed for IgM antibodies against coxsackie B virus serotypes 1 through 5 by a Ix-antibody capture radio immunoassay technique. Sera from 94 referent children matched for age, sex and residential area, collected during the same period, were also analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…4 Enterovirus infection(s) might be involved in the development of type 1 diabetes, 3,[5][6][7] even though some studies are contradicting. [8][9][10] Our previous epidemiological investigations clearly speak about the existence of inverse association between the prevalence of enterovirus infections and frequency of type 1 diabetes in background population. 11,12 Based on these findings we have launched "polio hypothesis" according to which the increase in type 1 diabetes incidence in some countries is due to a change in the epidemiology of enterovirus infections.…”
Section: Enterovirus Infections In Young Infantsmentioning
confidence: 87%
“…4 Enterovirus infection(s) might be involved in the development of type 1 diabetes, 3,[5][6][7] even though some studies are contradicting. [8][9][10] Our previous epidemiological investigations clearly speak about the existence of inverse association between the prevalence of enterovirus infections and frequency of type 1 diabetes in background population. 11,12 Based on these findings we have launched "polio hypothesis" according to which the increase in type 1 diabetes incidence in some countries is due to a change in the epidemiology of enterovirus infections.…”
Section: Enterovirus Infections In Young Infantsmentioning
confidence: 87%
“…In previous studies no association between these virus infections and the onset of Type 1 diabetes was found [5][6][7]. Although mumps infection may result in transient ICA, islet cell surface antibodies and insulin-autoantibody responses [t9 -20], and may occasionally cause Type i diabetes [21], there is little evidence that these viruses are a significant cause of Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the difference in prevalence between ICA positive and negative individuals was not statistically significant, a study of larger numbers would be required to exclude such an association. A number of serological studies have found a higher prevalence of coxsackie B virus-specific IgM responses in patients at Type 1 diabetes onset compared with control subjects [5,8,9,22] while others have not [6][7]. In one study, the prevalence of IgM among Type i diabetic patients showed considerable geographic and temporal variation, ranging from 0-76 % [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coxsackie viruses and/or a greater frequency of positive serotests for several enteroviruses when comparing cases and control subjects [5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Several of the 'negative' studies deserve comment.…”
Section: For Debatementioning
confidence: 99%